2018
DOI: 10.1016/j.antiviral.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and biological rationale of repurposing sunitinib and erlotinib for dengue treatment

Abstract: There is an urgent need for strategies to combat dengue virus (DENV) infection; a major global threat. We reported that the cellular kinases AAK1 and GAK regulate intracellular trafficking of multiple viruses and that sunitinib and erlotinib, approved anticancer drugs with potent activity against these kinases, protect DENV-infected mice from mortality. Nevertheless, further characterization of the therapeutic potential and underlying mechanism of this approach is required prior to clinical evaluation. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 54 publications
1
82
0
1
Order By: Relevance
“…These included a number of oncology drugs such as sunitinib and erlotinib, both of which have been shown to inhibit viral infection of cells through the inhibition of AAK1. 5 However, these compounds bring serious side-effects, and our data infer high doses to inhibit AAK1 effectively. We do not consider these drugs would be a safe therapy for a population of sick and infected people.…”
Section: Baricitinib As Potential Treatment For 2019-ncov Acute Respimentioning
confidence: 70%
“…These included a number of oncology drugs such as sunitinib and erlotinib, both of which have been shown to inhibit viral infection of cells through the inhibition of AAK1. 5 However, these compounds bring serious side-effects, and our data infer high doses to inhibit AAK1 effectively. We do not consider these drugs would be a safe therapy for a population of sick and infected people.…”
Section: Baricitinib As Potential Treatment For 2019-ncov Acute Respimentioning
confidence: 70%
“…The drug targets are members of the numbassociated kinase (NAK) family-including AAK1 and GAK-the inhibition of which has been shown to reduce viral infection in vitro. 5,6 Baricitinib was identified as a NAK inhibitor, with a particularly high affinity for AAK1, a pivotal regulator of clathrin-mediated endocytosis. We suggested that this drug could be of use in countering SARS-CoV-2 infections, subject to appropriate clinical testing.…”
Section: Covid-19: Combining Antiviral and Anti-inflammatory Treatmentsmentioning
confidence: 99%
“…Other AI-algorithm-predicted NAK inhibitors include a combination of the oncology drugs sunitinib and erlotinib, shown to reduce the infectivity of a wide range of viruses, including hepatitis C virus, dengue virus, Ebola virus, and respiratory syncytial virus. 5,6 However, sunitinib and erlotinib would be difficult for patients to tolerate at the doses required to inhibit AAK1 and GAK. By contrast, at therapeutic doses used for the treatment of patients with rheumatoid arthritis, the free plasma concentrations of baricitinib are predicted to be sufficient to inhibit AAK1, and potentially GAK, in cellbased assays.…”
Section: Covid-19: Combining Antiviral and Anti-inflammatory Treatmentsmentioning
confidence: 99%
“…Erlotinib, another anticancer drug, also inhibits HCV entry and assembly. Similarly, sunitinib and/or erlotinib can restrict infection by DENV and EBOV in vitro and in a murine animal model and have potent in vitro antiviral activity against ZIKV, WNV, CHIKV, Junin virus (JUNV) and respiratory syncytial virus (RSV) (Bekerman et al, 2017;Pu et al, 2018). Sunitinib has also been shown to inhibit HCMV infection in cell culture (Cai et al, 2014) and HIV-1 infection of resting CD4 T cells (Guo et al, 2013).…”
Section: Sunitinib and Other Tyrosine Kinase Inhibitorsmentioning
confidence: 99%